The world of lupus - Hughes, Graham (Henry Stewart Talks, 2017)
History, Serological changes, Lessons from patients, Diagnosis, Lupus around the world, Treatments failures and successes, Treatment options: 2017, Anti-malarial treatment, Plaquenil, New therapies for SLE